An Investigation on Dietetics and Nutritional Interests using Quantitative Analysis in the Existing Prevalent Conditions of COVID-19 - Mary Henrietta H.; Stanley Raj A.; Megavathi M.; Kavinil V.; Giridharan B. (Journal of Human Health Research, 2021)
This paper wishes to address the main concerns of food patterns and food consumption during the epidemic with quantitative analysis from various regions of Tamil Nadu. It was noted that it is more important than natural foods. The current epidemic had a profound effect on the humankind, recognizing the importance of staying healthy is the crucial aspect. In time, further research was conducted on the diet of the Indian subcontinent. Everyone should know about the importance of health and how nutrition contributes to the health and equality of people around the world. The main purpose of this study was to identify the importance of good nutrition and disease prevention.
Keywords: Healthy Eating